PERANCANGAN RUSUNAWA TPI 4 LANTAI DI JALAN PEMBANGUNAN KECAMATAN PONTIANAK BARAT KOTA PONTIANAK - Nathania, Stella; Mahendra, Erick; Rosanti, Indah; Riyanti, Rika (RETENSI, 2023)
ABSTRACT The development of housing is one of the primary needs that must be met for human survival. As time goes on, humans grow very quickly with the increasing need for housing, also economically for the lower middle class people, the more diverse jobs that require people to no longer be able to own a house because of land and expensive housing prices. Therefore we need a place to live that can be inhabited en masse for low-income people. For the sake of creating an ideal urban and population structure, rental flats can be one solution. Planning and designing rental flats that are livable and a healthy, safe, harmonious, and sustainable environment as well as creating integrated settlements to build economic, social and cultural. In the design of graded building is important to note several criteria, referring to The Regulation of Minister of Public Housing of Republic Indonesian Number 10 in 2012 is about Implementation of Housing and Residential Areas with Balanced Occupancy. In this writing, the design of TPI Rental Flats is using site location data, namely residential areas with an area according to the selected location is very open to developing flats that are integrated with the surrounding residential environment as well as environmental data around the site, such as sun and wind. Based on design result, it was obtained that the design concept of TPI Rental Flats in Pontianak is emphasized on Metaphor concept, so in design can representing livable life for low-income residents. Then the rooms designed in the TPI Rental Flats are consist of 3 types, namely type 36 as many 20 rooms, type 45 as many 15 rooms and type 60 as many 20 rooms with a total occupant of 737 persons. In calculating the reservoir requirements, the volume of the upper reservoir is 60.4 m3 with dimensions of 2 x 8 x 1.2 m for 2 pieces, while the lower reservoir is 90.6 m3 with dimensions of 4 x 8 x 1.8 m for 1 unit. In designing a fire protection system, the number of hydrants used in the building is 9 with a volume of 410400 liters, the number of yard hydrants used is 9 with a volume of 1539000 liters and the number of sprinklers used is 454 with a volume of 232902 liters, so that the total water requirement is 2182302 liters. For designing the dimensions of the structure, the dimensions of the columns used are 50x50 cm and the dimensions of the main beams and the joists respectively are 35x75 cm and 25x50 cm. Keywords: rental flats building, design, metaphor concept (human)